Substrates Preparation from Woody Tropical Waste Biomass for Biohydrogen Production - Susilaningsih, Dwi; Harwati, Theresia Umi; Anam, Khairul; Yopi, Yopi (UI Scholars Hub, 2008)
Substrates Preparation from Woody Tropical Waste Biomass for Biohydrogen Production. Addressing to the global warming problem, energy crisis and pollution, hydrogen production by micro-organisms using biotechnological approach should be considered, since it fulfils the recent society requirement to safely produce, renewable and environmental friendly energy. Hydrogen is one of the most promising green energy sources, because it is easily converted to electricity and cleanly combustible. There are three types of micro-organisms for hydrogen production, the first is cyanobacteria through the photosynthesis process, the second is anaerobic bacteria, which use organic substances as electron donor and energy and convert them to hydrogen, the third is photosynthetic bacteria, somewhat between photosynthetic and anaerobic bacteria, which are capable of converting the organic substances to hydrogen at a fairly high rate. We propose to use the abundant waste biomasses in Indonesia for hydrogen production by the microbial system. Our focus research is the production of hydrogen from waste biomasses by two-stage fermentation systems, which combine the conversion process of monomer biomasses to lactic acid by Lactobacillus sp. and the conversion process of lactic acid to hydrogen by photosynthetic bacteria. In this research, two kind substrates preparation were apply for woody waste biomass such as chemical hydrolysis and biological methods with several treatments. The results of the substrate preparation state showed that hydrolyses process of biomasses using strong acid are yielded total sugar about 70-90% of previous original content. Moreover, hydrolyses process using weak/diluted acid are yielded total sugar about 4-30% of original sugar. Furthermore, the biological treatments of degradation of woody waste biomasses are yielded total sugar about 0-10% (by single culture) and 10-50% (by consortium). Those hydrolysates substrates will use for fermentation two stages of lactate fermentation and conversion by photosynthetic bacteria in order to produce hydrogen gas.